Comparative analysis of ternary lithium batteries and lithium iron phosphate - Liu Ruoxuan (E3S Web of Conferences)
Ternary lithium batteries (TLB) and lithium iron phosphate batteries (LIPB) are two popular battery types in the current battery market. They have their own advantages and disadvantages in performance and application areas. Through the analysis of the structure, performance and application of the two types of batteries, it can be seen that the anode of TLB is an octahedral structure with high energy density, strong fast charging ability and excellent low temperature discharge performance. The different ratios of nickel, cobalt and manganese in the anode material are suitable for a variety of unused occasions. However, the high-temperature stability of TLB is poor, and thermal runaway is easy to occur at high temperatures, and their cycle life is relatively short. LIPB are known for their high safety, long cycle life and relatively low cost. Its unique olivine crystal structure and stable P-O covalent bonds give it excellent thermal stability, even at high temperatures, the battery will not easily decompose. The disadvantages of LIPB are mainly reflected in their lower energy density and low-temperature discharge performance. Combining the advantages of the two materials to develop a new battery material with both high energy density and high safety will be an important research direction in the future.